Livestock solutions to regenerate soils and landscapes for sustainable agri-food systems transformation in Africa - Paul, Birthe K.; Mutegi, James; Wironen, Michael; Wood, Stephen; Peters, Michael; Nyawira, Sylvia; Misiko, Michael; Dutta, Sudarshan; Zingore, Shamie; Oberthür, Thomas; Notenbaert, An Maria Omer; Cook, Simon E. (SAGE Publications, 2023)
Agri-food systems approaches have gained international recognition over the last years. The role of livestock—both in mixed crop-livestock and pastoral systems—in sustainable agri-food systems transformation remains contested. In this review paper we present new analyses of original data from an international livestock expert survey, a quantitative search in Web of Science, and a literature review to unravel the potential for livestock systems to sustainably transform agri-food systems through regenerating soils and restoring degraded landscapes. We (i) illustrate how livestock is important for people and planet alike; (ii) review how to harness livestock's potential for rehabilitation of soils and landscapes; (iii) demonstrate successful case studies of livestock solutions such as improved forages for cut-and-carry systems and grazing management; and (iv) identify four critical steps required for lasting change at continental scale. We conclude that livestock solutions can be key catalysts for sustainable agri-food systems transformation that merit accelerated public and private investments. More research is needed to develop concrete, operational and practical livestock solutions, and measure, monitor and report their contributions and progress toward the 2030 Agenda for Sustainable Development.